Improving Oxidation Stability and Insulation Performance of Plant-Based Oils for Sustainable Power Transformers - Samson Okikiola Oparanti; Issouf Fofana; Reza Jafari (Physchem, 2025)
In power transformers, insulating liquids are essential for cooling, insulation, and condition monitoring. However, the environmental impact and biodegradability issues of traditional hydrocarbon-based liquids have spurred interest in green alternatives like natural esters. Despite their benefits, natural esters are highly prone to oxidation, limiting their broader use. This study explores a novel blend of two plant-based oils, canola oil and methyl ester derived from palm kernel oil, enhanced with two antioxidants, Tert-butylhydroquinone (TBHQ) and 2,6-Di-tert-butyl-4-methyl-phenol (BHT), to improve oxidation resistance. The performance of this antioxidant-infused oil was evaluated in terms of its interaction with Kraft paper insulation through accelerated thermal aging over periods of 10, 20, 30, and 40 days. Key properties, including the viscosity, breakdown voltage, conductivity, and FTIR spectra of oils, were analyzed before and after aging. Additionally, the degradation of the Kraft paper was investigated using scanning electron microscopy (SEM), optical microscopy, and dielectric strength tests. The results show that the antioxidant-treated oil exhibits significantly enhanced molecular stability, reduced viscosity, lower conductivity, and improved breakdown voltage (53.16 kV after 40 days). Notably, the oil mixture maintained the integrity of the Kraft paper insulation better than traditional natural esters, demonstrating superior dielectric properties and a promising potential for more sustainable and reliable power transformer applications.